KETERAMPILAN BERPIKIR MATEMATIS TINGKAT TINGGI SISWA MADRASAH ALIYAH DITINJAU DARI GENDER DAN STATUS SEKOLAH - Ibrahim Ibrahim (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This study examines higher order mathematical thinking skills in terms of differences in school status (public and private) and gender differences (male and female). All madrasah aliyah students in the city of Yogyakarta became the subject of this research population. The sample subjects of this study were 83 students from one public school and four private schools which were selected using a stratified sampling technique. The Higher Order Mathematical Thinking Skills Test became the instrument in this study. Two-way analysis of variance is the technical data analysis used in this study. This study concludes that students' high order mathematical thinking skills are still low. This study also concluded that there was no difference between the higher order mathematical thinking skills of public madrasah aliyah students and private madrasah aliyah students and there was no difference between the higher order mathematical thinking skills of female and male students. Another conclusion is that there is no interaction between school status and student gender on higher order mathematical thinking skills.